2020
DOI: 10.1080/21614083.2020.1834762
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Integrating a Mobile Decision-Support App into a Multicomponent CME Initiative: Developing Clinician Competence at the Point of Care

Abstract: Mobile health (mHealth) technologies such as smartphone applications are increasingly being adopted in the healthcare setting to support the delivery of evidence-based care. Given the approaching ubiquity of mHealth tools in medical practice, it is incumbent on the continuing medical education (CME) community to understand how these tools can be leveraged to develop clinician knowledge and competence, and how we can assess these educational outcomes. In this report, we describe our experience developing and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In this study, nurses used PubMed4Hh apps on their devices during meetings and at nursing stations, which is an encouraging behavior indicating their dedicated usage of scientific evidence in their practice. Point-of-care decision-support instruments provide real-world insights on the continuing medical education community 20 . Mobile health apps are beneficial for nurses to access relevant and credible health information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, nurses used PubMed4Hh apps on their devices during meetings and at nursing stations, which is an encouraging behavior indicating their dedicated usage of scientific evidence in their practice. Point-of-care decision-support instruments provide real-world insights on the continuing medical education community 20 . Mobile health apps are beneficial for nurses to access relevant and credible health information.…”
Section: Discussionmentioning
confidence: 99%
“…19 The new generation of nurses has grown up with technology and is mobile health savvy and comfortable with smartphones; a mobile device can be utilized as a decision-making instrument. Mobile health (eg, smartphone applications [apps]) has become a growing field of innovation 20 and has many advantages for clinicians to access services anywhere at any time. The near ubiquity and adoption of information technology and data systems in healthcare and the steady growth of younger nurses entering the workforce mean that nurses, especially during periods of public health emergencies and crises, provide an optimal pool of potential users for evidence-based mobile health apps (eg, mental health support apps).…”
Section: Evidence-based Practice In Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies presented evidence on user experiences of m-linked POC diagnostics. The included articles comprised two cross-sectional studies [24,25], two qualitative studies [26,27], a cohort study [28], three surveys [29][30][31], and one mixed method study [32].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Three studies were conducted in the United States of America (USA) [25,27,31], one in Ghana [26], one in South Africa [24], one in the United Kingdom (UK) [29], one in Australia [32], and one in Germany [30]. A cohort study by Jacobson et al (2020) also reported findings from the USA, Australia, Germany, Italy, Spain, Ireland, Brazil, Portugal, India, and Argentina [28]. The m-linked POC diagnostic technology presented in the included studies was focused on the following diagnostics (Fig.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%